From Anatolia to Aceh: Ottomans, Turks, and Southeast Asia By A. C. S. Peacock & Annabel Teh Gallop, eds. (Oxford: Oxford University Press, 2015. 348 pages.) (American Journal of Islam and Society, 2016)
Scholars of Islam in Southeast Asia and the history of the Malay-Indonesianworld have long been aware of periods of intense contacts between the OttomanEmpire and the region. Most widely known in this context are the politicalexchanges between the Sultanate of Aceh and the Ottoman Empire ofthe sixteenth century in the face of Portuguese maritime domination in SoutheastAsia. Regional calls for Ottoman aid against the expanding Europeanpowers by Muslim rulers were voiced in the nineteenth century. Despite thislapse in documented political contacts, however, connections between the tworegions were also sustained and developed further throughout the interveningcenturies on a variety of levels, most prominently in the economic, religious,and intellectual spheres.Despite the pioneering work of scholars such as Anthony Reid since the1960s, these connections, including inter alia the holy cities and Yemen’sHadhramaut region, both important centers of Islamic learning for SoutheastAsian Muslims and the source of strong migrant communities settling in theMalay-Indonesian world, have received scant scholarly attention. It is againstthis background that the British Academy-funded research project “Islam,Trade, and Politics across the Indian Ocean” and the volume at hand, whichrepresents one of its major fruits, brings together new innovative research onall of the various aspects of this particular relationship. Hereby it must benoted that its scope extends at times well beyond the Ottoman era also intothe Republican era, and that, importantly, much of the documentary evidencerelied upon derives from newly discovered archival sources.The volume is divided into three thematic parts, preceded by two introductorychapters by the editors and Anthony Reid, respectively, which set thestage for the remainder of the book by reviewing the relationship’s general ...